Penguatan Literasi Kesehatan dan Keselamatan Berkendara pada Kader Kesehatan Sebaya sebagai Upaya Pencegahan Perilaku Berisiko di SMAN 1 Bandar - Dhiya Ayu Paramitha; Mutiara; Dyah Ayu Nurul Jannah; Imelia Febriliyanti; Elica Qothriena; Naufal Ilham Pangestu; Haritsah Baihaqi; Rr. Vita Nurlatif (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Adolescence is a transitional period that is vulnerable to various risk behaviors, including unsafe sexual activity, infectious diseases (HIV/AIDS, tuberculosis, malaria), and traffic accidents. This community service program aims to improve the effectiveness of comprehensive health education in strengthening health and safety literacy among peer health cadres (PMR) at SMAN 1 Bandar as a strategy to prevent risk behaviors. This study employed a quantitative approach using a one-group pretest-posttest design involving 50 PMR members. Data were collected using multiple-choice questionnaires administered via Google Forms. The intervention was delivered through interactive lectures and educational posters. The results showed an increase in knowledge levels, with the “Good” category rising from 62.0% to 88.0%, the “Moderate” category decreasing from 34.0% to 12.0%, and the “Poor” category declining from 4.0% to 0.0%. Comprehensive education has proven effective in consolidating the understanding of peer cadres, enabling them to possess credible literacy to act as peer educators.